Clues to the diagnosis of biliary atresia in neonatal cholestasis - Mehmet Ağın; Gökhan Tümgör; Murat Alkan; Önder Özden; Mehmet Satar; Recep Tuncer (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The purpose of this study was to identify important clues in differentiating biliary atresia (BA) from causes of neonatal cholestasis other than BA (non-BA) and establishing the reliability of current tests. Materials and Methods: Thirty-four patients with BA and 27 patients with non-BA cholestasis being monitored at the Çukurova University Medical Faculty, the Pediatric Gastroenterology Department and the Pediatric Surgery Department between 2009 and 2015 were retrospectively assessed. Results: Cases of early onset jaundice, acholic stool, gamma-glutamyl transferase (GGT) elevation, and absent or small gallbladder on ultrasonography (USG) were greater in the BA group, while the levels of consanguinity and splenomegaly were higher in the non-BA group. The highest positive predictive value and specificity was determined for a GGT level greater than 197 in addition to absent or small gallbladder on USG and acholic stool in the BA group. Moreover, the presence of acholic stool (97%) exhibited the highest sensitivity and accuracy in the diagnosis of BA. Conclusion: Pale stool, GGT elevation, and absent or small gallbladder on USG are the most reliable tests for diagnosing BA. We recommend that intraoperative cholangiography should be performed without waiting for further test results when a neonate or infant presents with acholic stool, high GGT values, and absent or small gallbladder on abdominal USG.